Memory and Gender Bending: Papelucho gay en dictadura by Juan Pablo Sutherland - Cabrera, Federico (2023)
The article analyzes the relationship between collective memory, gender identity and childhood memories in the book Papelucho gay en dictadura (2019) by Juan Pablo Sutherland (Chile, 1967). The theoretical and methodological approach understands literary practices as a particular type of social discourse and, from this point of view, articulates conceptual tools of the studies of collective memories and gender studies. In particular, the work recovers the notion of "gender bending" proposed by Sylvia Molloy as a critical reading and writing exercise that introduces the question of gender (the body and any practice that distances itself from the guidelines of the heteropatriarchal order) as a a strategy that destabilizes naturalized representations and/or dominant perspectives. The order of the article attends to the way in which the voice of the narrator/writer is constructed narratively and to the different rhetorical strategies through which references to collective memory and the construction of a sex-dissident identity are manifested. The conclusions present some reflections on the links between autobiographical writing, memory and gender that emerge from the work with the text.